A Vision for the International Polar Year 2007-2008 - National Research Council (The National Academies Press, 2004)
In 2007-2008, many nations around the world will host an intense, coordinated field campaign of polar observations, research, and analysis called the "International Polar Year." This report presents an overview of potential science themes, enabling technologies, and public outreach opportunities that can be used to focus International Polar Year on societal needs. The committee recommends that the U.S. scientific community and participating agencies use this opportunity to better understand environmental change and variability in the polar regions; explore new scientific frontiers ranging from the molecular to the planetary scales; and engage the public through varied educations and outreach activities.
Keywords: Earth Sciences

Reengineering the 2010 Census: Risks and Challenges - National Research Council (The National Academies Press, 2004)
At the request of the U.S. Census Bureau, the National Research Council’s Committee on National Statistics established the Panel on Research on Future Census Methods to review the early planning process for the 2010 census. This new report documents the panel’s strong support for the major aims of the Census Bureau’s emerging plan for 2010. At the same time, it notes the considerable challenges that must be overcome if the bureau’s innovations are to be successful. The panel agrees with the Census Bureau that implementation of the American Community Survey and, with it, the separation of the long form from the census process are excellent concepts. Moreover, it concurs that the critically important Master Address File and TIGER geographic systems are in dire need of comprehensive updating and that new technologies have the potential to improve the accuracy of the count. The report identifies the risks and rewards of these and other components of the Census Bureau’s plan. The report emphasizes the need for the bureau to link its research and evaluation efforts much more closely to operational planning and the importance of funding for a comprehensive and rigorous testing program before 2010.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Planning for the International Polar Year 2007-2008: Report of the Implementation Workshop - National Research Council (The National Academies Press, 2004)
The International Polar Year (IPY) 2007-2008 will be an internationally coordinated campaign of polar observations, research, and analysis that will further our understanding of physical and social processes in the polar regions, examine their globally-connected role in the climate system, and establish research infrastructure for the future. Within this context, the IPY will galvanize new and innovative observations and research while at the same time building on and enhancing existing relevant initiatives. It also will serve as a mechanism to attract and develop a new generation of scientists and engineers with the versatility to tackle complex global issues. In 2004, the National Academies' Polar Research Board organized a workshop to explore the challenges associated with these initiatives. Planning for the International Polar Year 2007-2008 summarizes the presentations and discussions from this workshop.
Keywords: Earth Sciences

The 2000 Census: Counting Under Adversity - National Research Council (The National Academies Press, 2004)
The decennial census was the federal government’s largest and most complex peacetime operation. This report of a panel of the National Research Council’s Committee on National Statistics comprehensively reviews the conduct of the 2000 census and the quality of the resulting data. The panel’s findings cover the planning process for 2000, which was marked by an atmosphere of intense controversy about the proposed role of statistical techniques in the census enumeration and possible adjustment for errors in counting the population. The report addresses the success and problems of major innovations in census operations, the completeness of population coverage in 2000, and the quality of both the basic demographic data collected from all census respondents and the detailed socioeconomic data collected from the census long-form sample (about one-sixth of the population). The panel draws comparisons with the 1990 experience and recommends improvements in the planning process and design for 2010. The 2000 Census: Counting Under Adversity will be an invaluable resource for users of the 2000 data and for policymakers and census planners. It provides a trove of information about the issues that have fueled debate about the census process and about the operations and quality of the nation’s twenty-second decennial enumeration.
Keywords: Behavioral and Social Sciences; Surveys and Statistics

Utilization of Operational Environmental Satellite Data: Ensuring Readiness for 2010 and Beyond - National Research Council (The National Academies Press, 2004)
Keywords: Earth Sciences; Space and Aeronautics

The Engineer of 2020: Visions of Engineering in the New Century - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2004)
To enhance the nation's economic productivity and improve the quality of life worldwide, engineering education in the United States must anticipate and adapt to the dramatic changes of engineering practice. The Engineer of 2020 urges the engineering profession to recognize what engineers can build for the future through a wide range of leadership roles in industry, government, and academia--not just through technical jobs. Engineering schools should attract the best and brightest students and be open to new teaching and training approaches. With the appropriate education and training, the engineer of the future will be called upon to become a leader not only in business but also in nonprofit and government sectors. The book finds that the next several decades will offer more opportunities for engineers, with exciting possibilities expected from nanotechnology, information technology, and bioengineering. Other engineering applications, such as transgenic food, technologies that affect personal privacy, and nuclear technologies, raise complex social and ethical challenges. Future engineers must be prepared to help the public consider and resolve these dilemmas along with challenges that will arise from new global competition, requiring thoughtful and concerted action if engineering in the United States is to retain its vibrancy and strength.
Keywords: Education

Space Studies Board Annual Report 2003 (The National Academies Press, 2004)

Reducing Future Flood Losses: The Role of Human Actions: Summary of a Workshop, March 2, 2004, Washington, DC: A Summary to the Disasters Roundtable - National Research Council (The National Academies Press, 2004)
On March 2, 2004 the Disasters Roundtable held its 10th workshop, which dealt with the topic of flood hazards and what needs to be done to help reduce societyï¿½s future vulnerability to them. The summary of the workshop, entitled Reducing Future Flood Losses: The Role of Human Actions, covers discussion by academic, government and private sector experts and stakeholders on the role of local, state and federal government in countering flood disaster losses; initiatives undertaken by the private sector; insights from research on such topics as presidential flood disaster declarations; and discussion of the historical evolution of government flood policies, including those initiated by Congress and implemented by various administrations through the Corps of Engineers and FEMA.
Keywords: Earth Sciences

Progress in Improving Project Management at the Department of Energy: 2003 Assessment - National Research Council (The National Academies Press, 2004)
In 1997, Congress, in the conference report, H.R. 105-271, to the FY1998 Energy and Water Development Appropriation Bill, directed the NRC to carry out a series of assessments of project management at the Department of Energy (DOE). This report, the 2003 Assessment, is the final one in that series. It presents an examination of DOE's progress in improving program management over the past three years including the Department's response to the recommendations of the previous assessments in this series. In addition to assessing DOE’s progress, the report also describes opportunities for further improvement and gives a prognosis for future developments.
Keywords: Energy and Energy Conservation; Transportation and Infrastructure

2003 Assessment of the Office of Naval Research's Marine Corps Science and Technology Program - National Research Council (The National Academies Press, 2004)
The Office of Naval Research (ONR) funds research across a broad range of scientific and engineering disciplines in support of the Navy and Marine Corps. To ensure that its investments are serving those ends and are of high quality, ONR requires each of its departments to undergo annual review. Since 1999, the Naval Expeditionary Warfare Department of ONR has requested that the NRC conduct these reviews. This report presents the results of the second review of the Marine Corps Science and Technology program. The first review was conducted in 2000. The 2003 assessment examines the overall Marine Corps S&T program, the littoral combat future naval capability, the core thrusts of the program, and basic research activities.
Keywords: Conflict and Security Issues; Space and Aeronautics

Report of the Treasurer to the Council for the Year Ended December 31, 2003 - National Academy of Sciences (The National Academies Press, 2004)

The Richard and Hinda Rosenthal Lectures 2003: Keeping Patients Safe -- Transforming the Work Environment of Nurses (The National Academies Press, 2004)
Through the generosity of the Rosenthal Family Foundation (formerly the Richard and Hinda Rosenthal Foundation), a discussion series was created to bring greater attention to some of the significant health policy issues facing our nation today. Each year a major health topic is addressed through remarks and conversation between experts in the field. The Institute of Medicine (IOM) later publishes the proceedings from this event for the benefit of a wider audience. This volume summarizes an engaging discussion on the IOM 2002 report, Keeping Patients Safe: Transforming the Work Environment of Nurses.
Keywords: Health and Medicine

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2003 NAE Symposium on Frontiers of Engineering - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2004)
This volume includes 14 papers from the National Academy of Engineering's Ninth Annual U.S. Frontiers of Engineering Symposium held in September 2003. The U.S. Frontiers meeting brings together 100 outstanding engineers (ages 30-45) to learn from their peers and discuss leading-edge technologies in a range of fields. The 2003 symposium covered these four areas: environmental engineering; fundamental limits of nanotechnology; counterterrorism technologies and infrastructure protection; and biomolecular computing. Papers in the book cover topics such as microbial mineral respiration; water-resource engineering, economics, and public policy; frontiers of silicon CMOS technology; molecular electronics; biological counterterrorism technologies; Internet security; DNA computing by self-assembly; and challenges in programming living cells, among others. A talk by Aerospace Corp. president and CEO William F. Ballhaus, Jr. titled The Most Important Lessons You Didn't Learn in Engineering School is also included in the volume. Appendixes include summaries of the breakout session discussion that focused on public understanding of engineering, information about the contributors, the symposium program, and a list of the meeting participants. The book is the ninth in a series covering the topics of the U.S. Frontiers of Engineering meetings.
Keywords: Education; Health and Medicine

The Development of Science-based Guidelines for Laboratory Animal Care: Proceedings of the November 2003 International Workshop - National Research Council (The National Academies Press, 2004)
The Development of Science-based Guidelines for Laboratory Animal Care is the summary of an international workshop held in Washington, DC, in November 2003 to bring together experts from around the world to discuss the available knowledge that can positively influence current and pending guidelines for laboratory animal care, identify gaps in that knowledge in order to encourage future research endeavors, and discuss the scientific evidence that can be used to assess the benefits and costs of various regulatory approaches affecting facilities, research, and animal welfare.
Keywords: Biology and Life Sciences; Agriculture

Adaptive Management for Water Resources Project Planning - National Research Council (The National Academies Press, 2004)
This book reviews the Corps of Engineers' experiences to date with the concept of “adaptive management” and provides advice on additional and more effective implementation of this planning approach. The adaptive management concept itself is complex and evolving, but might be summarized as “learning while doing.” The book reviews literature on adaptive management and notes that a range of adaptive management practices present themselves for Corps projects. It is noted that there is no “cookbook” approach to adaptive management, and the book encourages the Corps of Engineers to continue to work with and learn from its applications of the concept. To facilitate institutional learning and to ensure that experiences are being employed across the agency, the book recommends that a Corps Center for Adaptive Management be established. The book also notes that greater involvement from the administration and Congress will be essential to successful adaptive management applications, as the Corps' efforts in this area will benefit from clarified water resources management objectives, the authority to manage adaptively, and from resources necessary for programs such as stakeholder collaboration and post-construction evaluations.
Keywords: Earth Sciences

Water and Sustainable Development: Opportunities for the Chemical Sciences: A Workshop Report to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2004)
Experts in the areas of water science and chemistry from the government, industry, and academic arenas discussed ways to maximize opportunities for these disciplines to work together to develop and apply simple technologies while addressing some of the world’s key water and health problems. Since global water challenges cross both scientific disciplines, the chemical sciences have the ability to be a key player in improving the lives of billions of people around the world.
Keywords: Earth Sciences

Letter Report from the Panel for the Review of Proposals for NASA's Intelligent Propulsion Systems Foundation Technology (PSFT) Program (The National Academies Press, 2004)

Synthesis of Information Related to Transit Problems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's Transit Cooperative Research Program (TCRP) Research Results Digest 67: Synthesis of Information Related to Transit Problems provides information on the mission and goals of the TCRP synthesis program, and describes the progress and status of TCRP synthesis projects.
Keywords: Transportation and Infrastructure

Systems Integration for Project Constellation: Letter Report - National Research Council (The National Academies Press, 2004)
With the announcement of the Vision for U.S. Space Exploration, NASA has formed a new Exploration Systems Enterprise charged with development of systems to be used in the exploration of the moon, Mars, and other destinations. A key component of that enterprise is Project Constellation which is responsible for all of the systems necessary for human exploration. It is essential that those systems be integrated effectively for the mission to succeed. To assist with this objective, NASA asked the NRC to assess the relative merits of seven approaches for systems integration. This letter report presents this assessment. It provides a list of 21 criteria for judging the capability of each of the approaches to succeed in this complex integration task, and ratings of how well each can fulfill those criteria
Keywords: Space and Aeronautics

Preliminary Assessment of DOE Facility Management and Infrastructure Renewal: Letter Report - National Research Council (The National Academies Press, 2004)
The report that accompanied the House-approved Energy and Water Development Appropriations for FY2003 (H.Rept. 107-112) directed the National Research Council to evaluate the steps being taken by DOE to improve its facility and infrastructure management. Specifically, the NRC was to assess DOE’s facilities and infrastructure management practices; identify or develop “best practice” tools for DOE property management; develop guidelines for deciding when to repair, renovate, or replace facilities; and define performance metrics. This interim letter report presents the NRC’s preliminary assessment of DOE facility management policies and procedures and its current renewal activities. Seven broad-based attributes that characterize the quality of an organization’s facility management policies and practices were applied by the study committee in developing this assessment.
Keywords: Energy and Energy Conservation

Emerging Technologies and Ethical Issues in Engineering: Papers from a Workshop - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2004)
Engineers and ethicists participated in a workshop to discuss the responsible development of new technologies. Presenters examined four areas of engineering--sustainability, nanotechnology, neurotechnology, and energy--in terms of the ethical issues they present to engineers in particular and society as a whole. Approaches to ethical issues include: analyzing the factual, conceptual, application, and moral aspects of an issue; evaluating the risks and responsibilities of a particular course of action; and using theories of ethics or codes of ethics developed by engineering societies as a basis for decision making. Ethics can be built into the education of engineering students and professionals, either as an aspect of courses already being taught or as a component of engineering projects to be examined along with research findings. Engineering practice workshops can also be effective, particularly when they include discussions with experienced engineers. This volume includes papers on all of these topics by experts in many fields. The consensus among workshop participants is that material on ethics should be an ongoing part of engineering education and engineering practice.
Keywords: Engineering and Technology

Review of Travel Demand Modeling by the Metropolitan Washington Council of Governments: Second Letter Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
The TRB Committee for Review of Travel Demand Modeling by the Metropolitan Washington Council of Governments has issued the second of two letter reports to the National Capital Region Transportation Planning Board (TPB). This report reviews TPB’s proposed direction of future travel demand model upgrades. The first report reviewed performance of the TPB's travel forecasting model and processes for estimating mobile source emissions.Appendix A
Keywords: Transportation and Infrastructure

U.S. Army Corps of Engineers Water Resources Planning: A New Opportunity for Service - National Research Council (The National Academies Press, 2004)
From the Executive Summary: There are some concerns that the current Corps planning and construction budget has not kept pace with expanding national water management needs for flood hazard management, water transportation, and other purposes. At the same time, others question the wisdom of and budgetary prospects for the continuation of a traditional water project construction program. Debates about water use and funding priorities now extend to intense scrutiny of Corps of Engineers planning, investment, and project operations programs.
Keywords: Earth Sciences

Review of the Desalination and Water Purification Technology Roadmap - National Research Council (The National Academies Press, 2004)
The Bureau of Reclamation and Sandia National Laboratories jointly developed the Roadmap to serve as a strategic research pathway for desalination and water purification technologies to meet future water needs. The book recommends that the Roadmap include a sharper focus on the research and technological advancements needed to reach the long-term objectives. The book also suggests that the environmental, economic, and social costs of energy required by increased dependence on desalination be examined. Strategies for implementing the Roadmap initiative are provided.
Keywords: Environment and Environmental Studies; Earth Sciences

Groundwater Fluxes Across Interfaces - National Research Council (The National Academies Press, 2004)
Estimates of groundwater recharge and discharge rates are needed at many different scales for many different purposes. These include such tasks as evaluating landslide risks, managing groundwater resources, locating nuclear waste repositories, and estimating global budgets of water and greenhouse gasses. Groundwater Fluxes Across Interfaces focuses on scientific challenges in (1) the spatial and temporal variability of recharge and discharge, (2) how information at one scale can be used at another, and (3) the effects of groundwater on climate and vice versa.
Keywords: Earth Sciences; Environment and Environmental Studies

Transit-Oriented Development in the United States: Experiences, Challenges, and Prospects - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's Transit Cooperative Research Program (TCRP) Report 102: Transit-Oriented Development in the United States--Experiences, Challenges, and Prospects examines the state of the practice and the benefits of transit-oriented development and joint development throughout the United States.
Keywords: Transportation and Infrastructure

Review of the Centers for Disease Control and Prevention's Smallpox Vaccination Program Implementation: Letter Report #6 - Institute of Medicine (The National Academies Press, 2004)
Keywords: Health and Medicine

Tenth Interim Report of the Subcommittee on Acute Exposure Guideline Levels - National Research Council (The National Academies Press, 2004)
Keywords: Environment and Environmental Studies

Transit Design, Construction, and Operations in the Mediterranean Region - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Research Results Digest 66: Transit Design, Construction, and Operations in the Mediterranean Region provides an overview of an international transit studies mission that investigated transit design, construction, and operation in Athens, Greece, and in Naples, Rome, and Milan, Italy.
Keywords: Transportation and Infrastructure

Recommended Mechanistic-Empirical Pavement Design Guide and Software: Available for Evaluation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 290: Recommended Mechanistic-Empirical Pavement Design Guide and Software: Available for Evaluation announces the availability of key products from Development of the 2002 Guide for the Design of New and Rehabilitated Pavement Structures: Phase II project.Information on downloading a research version of the Mechanistic-Empirical Pavement Design Guide and Software.
Keywords: Transportation and Infrastructure

Smaller Facilities: Letter Report - National Research Council (The National Academies Press, 2004)
The Committee on Smaller Facilities is review the current state of small and mid-sized facilities for materials research in the United States at the request of NSF and DOE. Such facilities play a major role in materials research, but they are widely considered to be less than optimally developed or used. To address this concern, the NRC was asked to assess these facilities to help determine ways to use them more effectively. This letter report presents key topics that the committee will explore in depth to carry out this assessment. In particular, the study will assess the characteristics of successful smaller facilities and challenges they face. Recommendations will be provided to enhance the effectiveness of such facilities in performing materials research.
Keywords: Engineering and Technology

Lessons Learned from Workshop on Novel Approaches to Carbon Management: Letter Report - National Research Council (The National Academies Press, 2004)
One approach to the problem of carbon dioxide buildup in the Earth’s atmosphere is to develop novel ways to sequester CO2 before it enters the atmosphere or to accelerate its removal once it has. In order to determine whether this approach was feasible and practical, DOE asked the NRC help foster the identification of such novel concepts. A three-step project was launched to meet that request: a workshop on novel approaches; an evaluation of proposals in response to a DOE solicitation for developing such concepts; and an assessment of the process including lessons learned. The NRC delivered reports on the first two steps in April and September 2003, and this letter report presents the results of the last step of the project. The report presents an assessment of the workshop, the solicitation process, and the NRC role. In addition, recommendations are provided for improving the process for subsequent DOE carbon management initiatives.
Keywords: Environment and Environmental Studies

Reviewing Federal Railroad Research, Development, and Demonstration Programs: Letter Report #3 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
The TRB Committee for Review of the Federal Railroad Administration (FRA) Research, Development, and Demonstration Programs has issued its third letter report to the FRA. The report offers observations and recommendations on the overall direction of FRA’s research, development, and demonstration programs; examines specific areas currently in progress or being planned within the Railroad R&D Program; addresses FRA’s request or recommendations on future directions for the Next Generation High-Speed Rail Technology Demonstration program; reviews contextual research; and offers suggestions for the agenda of the committee’s fall meeting.
Keywords: Transportation and Infrastructure

Highway Capacity Manual Applications Guidebook (NCHRP Research Results Digest 287) - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 287: Highway Capacity Manual Applications Guidebook summarizes the contents of the Highway Capacity Manual Applications Guidebook , which uses real-world case studies to illustrate how the Highway Capacity Manual and other analysis tools can be used.
Keywords: Transportation and Infrastructure

Quality Characteristics and Test Methods for Use in Performance-Related Specifications of Hot Mix Asphalt Pavements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 291: Quality Characteristics and Test Methods for Use in Performance-Related Specifications of Hot Mix Asphalt Pavements provides recommendations for simple, practical, and rapid test methods to measure quality characteristics of as-produced and as-constructed hot mix asphalt.
Keywords: Transportation and Infrastructure

Letter Report on the Freight Analysis Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
A letter report from TRB’s Committee on the Future of the Federal Highway Administration’s (FHWA’s) Freight Analysis Framework (FAF) summarizes the outcomes of the committee’s October 2003 workshop on the FAF. The report recommends that FHWA’s Freight Office focus its resources on developing a national freight data program that builds on lessons learned in the FAF project. Further work on the FAF itself should be restricted to short-term documentation and clarification efforts and some limited updating.
Keywords: Transportation and Infrastructure

Immunization Safety Review: Vaccines and Autism - Institute of Medicine (The National Academies Press, 2004)
This eighth and final report of the Immunization Safety Review Committee examines the hypothesis that vaccines, specifically the measles-mumps-rubella (MMR) vaccine and thimerosal-containing vaccines, are causally associated with autism. The committee reviewed the extant published and unpublished epidemiological studies regarding causality and studies of potential biologic mechanisms by which these immunizations might cause autism. Immunization Safety Review: Vaccines and Autism finds that the body of epidemiological evidence favors rejection of a causal relationship between thimerosal-containing vaccines and autism. The book further finds that potential biological mechanisms for vaccine-induced autism that have been generated to date are only theoretical. It recommends a public health response that fully supports an array of vaccine safety activities and recommends that available funding for autism research be channeled to the most promising areas. The book makes additional recommendations regarding surveillance and epidemiological research, clinical studies, and communication related to these vaccine safety concerns.
Keywords: Health and Medicine

River Basins and Coastal Systems Planning Within the U.S. Army Corps of Engineers - National Research Council (The National Academies Press, 2004)
The U.S. Army Corps of Engineers (the Corps) has played a large and important role in shaping water resources systems in the United States since Congress first tasked it in 1824 to improve navigation on the Ohio and Mississippi Rivers. Since then, rivers have been modified for navigation and flood control, harbors have been dredged for shipping, and coastlines are routinely fortified against erosion and beach loss. Recent decades have seen an overall decline in budgets for civil works project construction, yet the range of objectives for water resources projects has broadened as society places more value on environmental and recreational benefits. Thus, the Corps' portfolio of water resources projects has changed considerably. There is a reduced emphasis on traditional construction projects and an increased focus on maintenance and reoperation of existing projects such as locks, dams, and levees and on environmental restoration projects. An integrated approach to water resources planning at the scale of river basins and coastal systems is widely endorsed by the academic and engineering communities. The Corps' mission, expertise, and experience give it immense potential to alter the structure and functioning of the nation's waterways and coasts. As might be expected in a large and complex organization answering to a range of public and private demands, implementation of these new policies and objectives is neither consistent nor complete. River Basins and Coastal Systems Planning within the U.S. Army Corps of Engineers recommends improvements in the Corps' water resource project planning and review process. This report compares economic and environmental benefits and costs over a range of time and space scales, suggests multiple purpose formulation and evaluation methods, and recommends integration of water development plans with other projects in the region.
Keywords: Earth Sciences

Vehicle Systems Panel Report on the Status of NASA's Vehicles Systems Program: Letter Report - National Research Council (The National Academies Press, 2004)
In November 2003, ASEB released a report, An Assessment of NASA’s Aeronautics Technology Programs. After the release, NASA requested the NRC to reconvene the Panel on Vehicle Systems Program, which had been established as part of the study infrastructure for the report. Specifically, NASA wanted an evaluation of the progress made by the Program in formulating and directing its activities over the past nine months (since March 2003). This letter report presents the findings of that review. In almost all cases, the recommendations contained in this letter report, amplify and reinforce those contained in the full report.
Keywords: Space and Aeronautics

Review of Science Requirements for the Terrestrial Planet Finder: Letter Report - National Research Council (The National Academies Press, 2004)
The NRC, in its 2000 report, Astronomy and Astrophysics in the New Millennium, ranked the Terrestrial Planet Finder (TFP) project third among major NASA missions and sixth overall in its research priority recommendations to NASA for the coming decade. In January 2004, NASA asked the NRC for an updated assessment of the TPF mission. In April 2004, NASA also announced its intention to proceed with both coronagrahic and interferometric planet finder missions (TPF-C and TPC-I) on an accelerated schedule. This letter report presents the findings of that updated assessment in light of NASA’s announcement. In it, the NRC concludes that the mission's goals are consistent with the 2000 report, but raises two primary concerns. First, the current schedule for TPF-C does not leave enough time for vital precursor missions, and second, proceeding with the TPF-C now would disrupt the scientific balance of NASA’s space science portfolio.
Keywords: Space and Aeronautics

Embracing Change in a Changing World -- Case Studies Applying New Paradigms for Rural and Small Urban Transit Service Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's Transit Cooperative Research Program (TCRP) Report 99: Embracing Change in a Changing World -- Case Studies Applying New Paradigms for Rural and Small Urban Transit Service Delivery includes case studies of how some transportation providers are addressing the opportunities and challenges of a rapidly changing rural environment.
Keywords: Transportation and Infrastructure

A Guide for Reducing Collisions Involving Heavy Trucks - Transportation Research Board (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Report 500 Volume 13: Guidance for Implementation of the AASHTO Strategic Highway Safety Plan -- A Guide for Reducing Collisions Involving Heavy Trucks provides strategies that can be employed to reduce the number of collisions involving heavy trucks.
Keywords: Transportation and Infrastructure

A Guide for Reducing Collisions at Signalized Intersections - Transportation Research Board (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Report 500 Volume 12: Guidance for Implementation of the AASHTO Strategic Highway Safety Plan -- A Guide for Reducing Collisions at Signalized Intersections provides strategies that can be employed to reduce the number of collisions at signalized intersections.
Keywords: Transportation and Infrastructure

Measuring Research and Development Expenditures in the U.S. Economy: Interim Report - National Research Council (The National Academies Press, 2004)
Keywords: Industry and Labor; Math, Chemistry, and Physics; Surveys and Statistics

A New Vision of Mobility: Guidance to Foster Collaborative Multimodal Decision Making - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) and National Cooperative Highway Research Program (NCHRP) have jointly produced Research Results Digest TCRP 65/NCHRP 288 -- A New Vision of Mobility: Guidance to Foster Collaborative Multimodal Decision Making. The single digest summarizes the results of the first phase of a TCRP and NCHRP jointly funded project that will eventually produce a short document for popular distribution, serving as a guidance resource in a “handbook” format and a “compendium” of case examples upon which the guidance document is based.
Keywords: Transportation and Infrastructure

Development of a Highway Safety Manual - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 286: Development of a Highway Safety Manual presents a summary of the results of a study that developed an annotated outline, prototype chapter, and work plan for the first edition of the Highway Safety Manual. More detailed information on the study is available in NCHRP Web Document 62: Development of a Highway Safety Manual.
Keywords: Transportation and Infrastructure

Appendixes to Measuring and Communicating the Effects of Traffic Incident Management Improvements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’ National Cooperative Highway Research Program (NCHRP) Web Document 64 is the appendixes to NCHRP Research Results Digest 289: Measuring and Communicating the Effects of Traffic Incident Management Improvements. It includes workshop presentations and examples traffic incident management promotional activities.
Keywords: Transportation and Infrastructure

Integral Steel Box-Beam Pier Caps - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 527: Integral Steel Box-Beam Pier Caps examines details, design methodologies, and specifications for integral connections of steel superstructures to concrete intermediate piers. The report also includes an example illustrating the design of the connection of the cap beam to the girders and column is also included.
Keywords: Transportation and Infrastructure

Confronting the Nation's Water Problems: The Role of Research - National Research Council (The National Academies Press, 2004)
In order to confront the increasingly severe water problems faced by all parts of the country, the United States needs to make a new commitment to research on water resources. A new mechanism is needed to coordinate water research currently fragmented among nearly 20 federal agencies. Given the competition for water among farmers, communities, aquatic ecosystems and other users—as well as emerging challenges such as climate change and the threat of waterborne diseases—Confronting the Nation's Water Problems concludes that an additional $70 million in federal funding should go annually to water research. Funding should go specifically to the areas of water demand and use, water supply augmentation, and other institutional research topics. The book notes that overall federal funding for water research has been stagnant in real terms for the past 30 years and that the portion dedicated to research on water use and social science topics has declined considerably.
Keywords: Earth Sciences; Environment and Environmental Studies

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 12, Transit Pricing and Fares - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 10 – Bus Routing and Coverage examines traveler response to, and related impacts of, conventional bus transit routing alterations. The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.

A Guide for Increasing Seatbelt Use - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Report 500 -- Guidance for Implementation of the AASHTO Strategic Highway Safety Plan; Volume 11: A Guide for Increasing Seatbelt Use provides strategies that can be employed to increase the use of seatbelts.Additional information on the NCHRP Report 500 series.
Keywords: Transportation and Infrastructure

Portable Scour Monitoring Equipment - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Report 515: Portable Scour Monitoring Equipment presents the findings of a research project undertaken to develop portable scour monitoring equipment for measuring streambed elevations at bridge foundations during flood conditions. The report provides specific fabrication and operation guidance for a portable scour monitoring device.
Keywords: Transportation and Infrastructure

Assessment of Options for Extending the Life of the Hubble Space Telescope: Letter Report - National Research Council (The National Academies Press, 2004)
Following the loss of the Space Shuttle Columbia and subsequent to the report of the board created to investigate the accident, NASA, citing safety reasons, decided to limit shuttle flights to International Space Station missions and to investigate other options for extending Hubble’s life. Congressional concern over this decision prompted it to ask for an independent assessment. In response the chair of the investigative board called for a study of the risks and benefits of using the shuttle for the servicing mission, and NASA subsequently asked the NRC for this study. This letter report presents preliminary findings and recommendations of that study. It urges NASA to commit to a servicing mission, notes that a proposed robotic mission would be quite complex and require significant development, and states that NASA should not preclude a shuttle servicing mission at this time. A final report will be released this fall.
Keywords: Space and Aeronautics

Equipment for Collecting Traffic Load Data - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 509: Equipment for Collecting Traffic Load Data identifies the key issues that should be considered by state and other highway operating agencies in selecting traffic equipment for collecting the truck volumes and load spectra needed for analysis and design of pavement structures.
Keywords: Transportation and Infrastructure

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 10, Bus Routing and Coverage - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 10 – Bus Routing and Coverage examines traveler response to, and related impacts of, conventional bus transit routing alterations.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Opportunities in High Magnetic Field Science: Letter Report - National Research Council (The National Academies Press, 2004)
In recent years the field of high magnetic field science has become increasingly important to other disciplines, including biology. In 2002, the National Science Foundation concluded that there was a need for an assessment of the field in the United States to set the stage for future planning. Accordingly, it requested that the NRC assess the current state and future prospects for high-magnetic-field science and instrumentation in the United States. This letter report provides a status report of that study. The letter report offers a brief assessment of the current position of the United States in this field and lists a series of questions that will be addressed in the final report.
Keywords: Math, Chemistry, and Physics

Measuring and Communicating the Effects of Traffic Incident Management Improvements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’ National Cooperative Highway Research Program (NCHRP) Research Results Digest 289: Measuring and Communicating the Effects of Traffic Incident Management Improvements examines performance measures for traffic incident management. Appendixes to NCHRP Research Results Digest 289 are available online.
Keywords: Transportation and Infrastructure

Short-Term Monitoring for Compliance with Air Quality Standards - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 479: Short-Term Monitoring for Compliance with Air Quality Standards provides transportation and air quality planners and decision makers with short-term monitoring procedures that can produce input data for predicting air quality exceedances without requiring the collection of large amounts of monitoring data.
Keywords: Transportation and Infrastructure

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 18, Parking Management and Supply - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 18 – Parking Management and Supply examines how travelers respond to differences in the supply and availability of vehicle parking, including changes that might occur as a result of shifting land-use patterns, changes in regulatory policy, or attempts to “manage” the supply of parking.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

A Guide for Reducing Collisions at Signalized Intersections - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 500 Volume 12: Guidance for Implementation of the AASHTO Strategic Highway Safety Plan -- A Guide for Reducing Collisions at Signalized Intersections provides strategies that can be employed to reduce the number of collisions at signalized intersections.
Keywords: Transportation and Infrastructure

Guideline and Recommended Standard for Geofoam Applications in Highway Embankments - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB National Cooperative Highway Research Program (NCHRP) Report 529: Guideline and Recommended Standard for Geofoam Applications in Highway Embankments includes a design guideline and recommended standard for geofoam applications in the design and construction of highway embankments.
Keywords: Transportation and Infrastructure

Track-Related Research Volume 3: Exothermic Welding of Heavy Electrical Cables to Rail -- Applicability of AREMA Track Recommended Practices for Transit Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's Transit Cooperative Research Program (TCRP) Report 71, volume 3: Track-Related Research Volume 3: Exothermic Welding of Heavy Electrical Cables to Rail -- Applicability of AREMA Track Recommended Practices for Transit Agencies evaluates current practices and possible improvements to methods of connecting heavy electrical cables to rail, and identifies areas where American Railway Engineering and Maintenance-of-Way Association (AREMA) recommended practices may not apply to transit operations. The report also identifies transit practices and components that are not addressed by AREMA recommended practices.
Keywords: Transportation and Infrastructure

Thermally Sprayed Metal Coatings to Protect Steel Pilings: Final Report and Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 528: Thermally Sprayed Metal Coatings to Protect Steel Pilings: Final Report and Guide investigtes thermally sprayed metal coatings (TSMCs) and offers a guide for the application of TSMCs to protect steel pilings from corrosion.
Keywords: Transportation and Infrastructure

A Guide for Reducing Collisions Involving Heavy Trucks - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 500 Volume 13: Guidance for Implementation of the AASHTO Strategic Highway Safety Plan -- A Guide for Reducing Collisions Involving Heavy Trucks provides strategies that can be employed to reduce the number of collisions involving heavy trucks.
Keywords: Transportation and Infrastructure

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 3, Park-and-Ride/Pool - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 3 – Park-and-Ride/Pool examines travel demand and related aspects of providing and supporting park-and-ride and park-and-pool facilities.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Access Management on Crossroads in the Vicinity of Interchanges - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 332: Access Management on Crossroads in the Vicinity of Interchanges examines current practices relating to access location and design on crossroads in the vicinity of interchanges. It identifies standards and strategies used on new interchanges and on the retrofit of existing interchanges.
Keywords: Transportation and Infrastructure

A Guide for Reducing Collisions Involving Older Drivers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Report 500 -- Guidance for Implementation of the AASHTO Strategic Highway Safety Plan Volume 9: A Guide for Reducing Collisions Involving Older Drivers provides strategies that can be employed to reduce the number of collisions involving older drivers.Additional information on the NCHRP Report 500 series.
Keywords: Transportation and Infrastructure

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 11, Transit Information and Promotion - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 11 – Transit Information and Promotion examines travelers’ responses to mass-marketed and targeted information and promotions, customer information services, and real-time transit information dissemination.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Cost-Effective Practices for Off-System and Local Interest Bridge - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 327: Cost-Effective Practices for Off-System and Local Interest Bridges examines off-system bridge design, construction, maintenance, financing, rehabilitation, and replacement. For this report, 'off-system' refers to those bridges typically owned and maintained by local agencies, and by state agencies on rural and other low-volume roads.
Keywords: Transportation and Infrastructure

Utilities and Roadside Safety - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB State of the Art Report 9: Utilities and Roadside Safety includes the latest information on utility company, state department of transportation (DOT), and local highway agency roadside safety programs; describes the current status of a combined federal and industry effort to implement roadside safety, including yielding poles; and documents recent developments in guardrail, concrete barrier, and crash cushion design to reduce utility maintenance costs, potential liability, and public health costs.
Keywords: Transportation and Infrastructure

Letter Report to the Bureau of Transportation Statistics - National Research Council (The National Academies Press, 2004)

State Product Evaluation Programs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 328: State Product Evaluation Programs examines the general use of evaluation programs within state departments of transportation (including the use of state specifications, and laboratory and field testing results), the national programs that exist to support the integration of new products and technologies into practice, and the general issues associated with conducting objective evaluations of new products and implementation of approved products.
Keywords: Transportation and Infrastructure

Operational Experiences with Flexible Transit Services - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 53: Operational Experiences with Flexible Transit Services examines transit agency experiences with “flexible transit services,” including all types of hybrid services that are not pure demand-responsive (including dial-a-ride and Americans with Disabilities Act paratransit) or fixed-route services, but that fall somewhere in between those traditional service models.
Keywords: Transportation and Infrastructure

Integrating Tourism and Recreation Travel with Transportation Planning and Project Delivery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 329: Integrating Tourism and Recreation Travel with Transportation Planning and Project Delivery provides an overview of current practice at transportation agencies, metropolitan planning organizations, state tourism and parks departments, federal land management agencies, and regional planning agencies. Overall, findings reveal that many state departments of transportation (DOTs) are now actively involved in tourism-related planning issues -- either proactively or in building solutions to infrastructure, access, or environmental issues that impinge on the success of tourism in the region.
Keywords: Transportation and Infrastructure

Pavement Management Applications Using Geographic Information Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 335: Pavement Management Applications Using Geographic Information Systems examines the state of the practice and knowledge of pavement management systems (PMS) using geographic information systems (GIS) and other spatial technologies, and discusses how the technologies have been combined to enhance the highway management process. The synthesis reviews the principal issues related to PMS data collection, integration, management, and dissemination; applications of spatial technologies for map generation and PMS spatial analysis; and implementation-related issues, including approaches used for integrating PMS and GIS and the different tools used to support pavement management decisions.
Keywords: Transportation and Infrastructure

Public Benefits of Highway System Preservation and Maintenance - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 330: Public Benefits of Highway System Preservation and Maintenance examines the current practices for identifying, measuring, and articulating the public benefits of highway system maintenance and operation, and of communicating those benefits that are understandable and meaningful to stakeholders—road users, elected officials, and others who have an interest in the system’s performance.
Keywords: Transportation and Infrastructure

Transit Operator Health and Wellness Programs - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 52: Transit Operator Health and Wellness Programs examines health and wellness issues faced by bus and rail operators, the impacts of these issues on operators’ abilities to be productive employees, and programs that transit agencies have implemented to improve the health status of operators.
Keywords: Transportation and Infrastructure

Letter Report to the FBI - National Research Council (The National Academies Press, 2004)
This letter report presents a review of actions taken by the FBI that address many of the concerns discussed in the NRC report, A Review of the FBI’s Trilogy Information Technology Modernization Program. That report was released in early May. The letter report presents the NRC assessment of those steps, noting where progress is apparent in addressing earlier concerns and where additional efforts are needed.

Solar and Space Physics and Its Role in Space Exploration - National Research Council (The National Academies Press, 2004)
In February 2004, the President announced a new goal for NASA; to use humans and robots together to explore the Moon, Mars, and beyond. In response to this initiative, NASA has adopted new exploration goals that depend, in part, on solar physics research. These actions raised questions about how the research agenda recommended by the NRC in its 2002 report, The Sun to the Earth and Beyond, which did not reflect the new exploration goals, would be affected. As a result, NASA requested the NRC to review the role solar and space physics should play in support of the new goals. This report presents the results of that review. It considers solar and space physics both as aspects of scientific exploration and in support of enabling future exploration of the solar system. The report provides a series of recommendations about NASA's Sun-Earth Connections program to enable it to meet both of those goals.
Keywords: Space and Aeronautics

Training Program for Night Road Work to Improve Safety and Operations - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 293: Training Program for Night Road Work to Improve Safety and Operations describes development of a self-contained training package that complements NCHRP Report 475: A Procedure for Assessing and Planning Nighttime Highway Construction and Maintenance, which presented a decision process to assist highway agencies in evaluating night work alternatives against other work schedules, and NCHRP Report 476: Guidelines for Design and Operation of Nighttime Traffic Control for Highway Maintenance and Construction, which provides guidelines for developing a plan for night work that will provide public and worker safety. The self-contained training package is available as NCHRP CD-ROM 50: Training Materials for Night Road Work to Improve Safety and Operations.
Keywords: Transportation and Infrastructure

Continuing Project to Synthesize Information on Highway Problems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 292: Continuing Project to Synthesize Information on Highway Problems outlines the NCHRP synthesis research process, and provides a list of ongoing and completed NCHRP synthesis reports.Suggestions for synthesis topics may be sent to NCHRP at any time by contacting the Cooperative Research Programs Staff, Transportation Research Board, 500 Fifth Street, NW, Washington D.C. 20001. You can also submit your recommendation at the NCHRP and TCRP Synthesis Suggestion Website. Topics suggested must be accompanied by a brief (one- or two-paragraph) scope statement including a discussion of the problem. A title (preferably no more than 10 words) and the name and affiliation of the submitter are also required. Identification of information sources would also be appreciated. Suggestions for updates of published syntheses are also welcome. A committee meets once each year, usually in the late spring, to make final selections from suggestions received through January 31 of the previous year. If a topic is not selected, the problem statement must be resubmitted the following year to be reconsidered.You are invited to express interest in being a consultant for a NCHRP or a consultant for a TCRP synthesis topic at any time.
Keywords: Transportation and Infrastructure

Transmission Pipelines and Land Use: A Risk-Informed Approach -- Special Report 281 - Transportation Research Board (The National Academies Press, 2004)
TRB Special Report 281: Transmission Pipelines and Land Use: A Risk-Informed Approach calls upon the U.S. Department of Transportation's Office of Pipeline Safety in the Research and Special Programs Administration to work with stakeholders in developing risk-informed land use guidance for use by policy makers, planners, local officials, and the public.
Keywords: Transportation and Infrastructure; Environment and Environmental Studies; Engineering and Technology

Significant Findings from Full-Scale Accelerated Pavement Testing - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 325: Significant Findings from Full-Scale Accelerated Pavement Testing documents and summarizes the findings from the various experimental activities associated with full-scale accelerated pavement testing programs.Errata: During the production process for this report a paragraph was inadvertently dropped from page 60,column one.Note: In November 2012 TRB released NCHRP Synthesis 433: Significant Findings from Full-Scale Accelerated Pavement Testing, which added to the base of knowledge created by NCHRP Synthesis 325.
Keywords: Transportation and Infrastructure

Individual Differences and the "High-Risk" Commercial Driver - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB's Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 4: Individual Differences and the “High-Risk” Commercial Driver explores individual differences among commercial drivers, particularly as these differences relate to the “high-risk” commercial driver. The synthesis identifies factors relating to commercial vehicle crash risk and assesses ways that the high-risk driver can be targeted by various safety programs and practices, at both fleet- and industry-wide levels.
Keywords: Transportation and Infrastructure

Eleventh Interim Report of the Subcommittee on Acute Exposure Guideline Levels - National Research Council (The National Academies Press, 2004)
Keywords: Environment and Environmental Studies

Public Transportation Operating Agencies as Employers of Choice - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 103: Public Transportation Operating Agencies as Employers of Choice documents principles, techniques, and strategies that are used in workforce recruitment, development, and retention. The report includes a companion document, Communications Strategy and Implementation Plan: Positioning the Public Transportation Operating Agency as an Employer of Choice, which describes strategies and solutions that offer the greatest potential for positioning public transportation operating agencies as employers of choice.
Keywords: Transportation and Infrastructure

Intelligent Sustainment and Renewal of Department of Energy Facilities and Infrastructure - National Research Council (The National Academies Press, 2004)
The United States Department of Energy's (DOE) facilities stewardship is extremely important to the department's ability to achieve its mission of protecting national, energy, and economic security with advanced science and technology and ensuring environmental cleanup. Intelligent Sustainment and Renewal of Department of Energy Facilities and Infrastructure evaluates the steps the department is taking to improve its facilities and infrastructure management. This report develops best-practice techniques for DOE real property asset management and guidelines for deciding when to repair, renovate, or replace DOE buildings.
Keywords: Engineering and Technology

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 9, Transit Scheduling and Frequency - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 9 – Transit Scheduling and Frequency examines scheduling changes made to conventional bus and rail transit, including changes in the frequency of service, hours of service, structuring of schedules, and schedule reliability.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

An Investigation of the Cause of Variation in HMA Bulk Specific Gravity Test Results Using Non-Absorptive Aggregates - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Web Document 66: An Investigation of the Cause of Variation in Hot-Mix Asphalt (HMA) Bulk Specific Gravity Test Results Using Non-Absorptive Aggregates investigates the cause of variation in relative density from the bulk test results.
Keywords: Transportation and Infrastructure

Load and Resistance Factor Design (LRFD) for Deep Foundations - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 507: Load and Resistance Factor Design (LRFD) for Deep Foundations examines resistance factors for driven pile and drilled shaft foundations,and provides a procedure for calibrating deep foundation resistance.Errata - Table 29 and Figure 47 in the pdf of NCHRP Report 507 contains incorrect information. An update to Table 29 and Figure 47 are available on-line.
Keywords: Transportation and Infrastructure

The Proteus Effect: Stem Cells and Their Promise for Medicine - Ann B. Parson (The National Academies Press, 2004)
Stem cells could be the key that unlocks cures to scores of diseases and illnesses. Their story is at once compelling, controversial, and remarkable. Part detective story, part medical history, The Proteus Effect recounts the events leading up to the discovery of stem cells and their incredible potential for the future of medicine. What exactly are these biological wonders – these things called stem cells? They may be tiny, but their impact is earth shaking, generating excitement among medical researchers – and outright turmoil in political circles. They are reported to be nothing short of miraculous. But they have also incited fear and mistrust in many. Indeed, recent research on stem cells raises important questions as rapidly as it generates new discoveries. The power of stem cells rests in their unspecialized but marvelously flexible nature. They are the clay of life waiting for the cellular signal that will coax them into taking on the shape of the beating cells of the heart muscle or the insulin-producing cells of the pancreas. With a wave of our medical magic wand, it’s possible that stem cells could be used to effectively treat (even cure) diseases such as Parkinson's disease, diabetes, heart disease, autoimmune disorders, and even baldness. But should scientists be allowed to pick apart four-day-old embryos in order to retrieve stem cells? And when stem cells whisper to us of immortality – they can divide and perpetuate new cells indefinitely – how do we respond? Stem cells are forcing us to not only reexamine how we define the beginning of life but how we come to terms with the end of life as well. Meticulously researched, artfully balanced, and engagingly told, Ann Parson chronicles a scientific discovery in progress, exploring the ethical debates, describing the current research, and hinting of a spectacular new era in medicine. The Proteus Effect is as timely as it is riveting.
Keywords: Biology and Life Sciences

Public Transportation Board Effectiveness: A Self-Assessment Handbook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 104: Public Transportation Board Effectiveness: A Self-Assessment Handbook provides a self-assessment process and tools to measure public transportation board effectiveness and provides references on how board characteristics can be changed to improve effectiveness in various areas. The Handbook also identifies the characteristics of public transportation boards that influence transit system performance.TRB’s Transit Cooperative Research Program (TCRP) Web Document 24: The Public Transportation Board Effectiveness Study describes the process used to develop the Public Transit Board Self-Assessment Handbook.
Keywords: Transportation and Infrastructure

Connection of Simple-Span Precast Concrete Girders for Continuity - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 519: Connection of Simple-Span Precast Concrete Girders for Continuity includes recommended details and specifications for the design of continuity connections for precast concrete girders. Also included in the report are examples illustrating the design of four precast girder types made continuous for live load.
Keywords: Transportation and Infrastructure

Strategies to Increase Coordination of Transportation Services for the Transportation Disadvantaged - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 105: Strategies to Increase Coordination of Transportation Services for the Transportation Disadvantaged examines strategies for initiating or improving coordination of local and regional publicly funded transportation services for the transportation disadvantaged.
Keywords: Transportation and Infrastructure

Traveler Response to Transportation System Changes Handbook, Third Edition: Chapter 6: Demand-Responsive/ADA - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s Transit Cooperative Research Program (TCRP) Report 95: Chapter 6 – Demand-Responsive/ADA includes traveler response and related information for services open to the general public and Americans with Disabilities Act (ADA) services intended for persons with disabilities.The Traveler Response to Transportation System Changes Handbook consists of these Chapter 1 introductory materials and 15 stand-alone published topic area chapters. Each topic area chapter provides traveler response findings including supportive information and interpretation, and also includes case studies and a bibliography consisting of the references utilized as sources.
Keywords: Transportation and Infrastructure

Analytical Methods and Approaches for Water Resources Project Planning - National Research Council (The National Academies Press, 2004)
Analytical Methods and Approaches for Water Resources Project Planningis part of a larger study that was conducted in response to a request from the U.S. Congress in the Water Resources Development Act of 2000 for the National Academy of Sciences to review the U.S. Army Corps of Engineer's peer review methods and analytical approaches. This report reviews the Corps' analytical procedures and planning methods, largely in the context of the federal Economic and Environmental Principles and Guidelines for Water and Related Land Resources Implementation Studies, also known as the Principles and Guidelines or "P and G" (P&G), as well as the Corps' Planning Guidance Notebook (PGN).
Keywords: Earth Sciences

Mapping Knowledge Domains (The National Academies Press, 2004)
Keywords: Computers and Information Technology

A Guide for Reducing Collisions Involving Pedestrians - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 500: Guidance for Implementation of the AASHTO Strategic Highway Safety Plan Volume 10: A Guide for Reducing Collisions Involving Pedestrians provides strategies that can be employed to reduce the number of collisions involving pedestrians.Additional information on the NCHRP Report 500 series.
Keywords: Transportation and Infrastructure

Safety of U-Turns at Unsignalized Median Openings - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 524: Safety of U-Turns at Unsignalized Median Openings includes recommended guidelines for locating and designing unsignalized median openings, and a methodology for comparing the relative safety performance of different designs.
Keywords: Transportation and Infrastructure

Relationship of Air Voids, Lift Thickness, and Permeability in Hot-Mix Asphalt Pavements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2004)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 531: Relationship of Air Voids, Lift Thickness, and Permeability in Hot-Mix Asphalt Pavements provides guidance for hot-mix asphalt pavement construction designed to achieve satisfactory levels of in-place air voids and permeability. This guidance was developed from the findings of a research project that examined the relationship of air voids content to permeability and hot-mix asphalt lift thickness. The full finding of the research were published as NCHRP Web Document 68.
Keywords: Transportation and Infrastructure